PERAN LEMBAGA PERBANKAN DALAM PEMBERDAYAAN PEREMPUAN - Lily Purnama; R. Hamdani Harahap; Beti Nasution (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
People's Business Credit (KUR) is a government program to increase Small, Micro, and Medium Enterprises (UMKM). Micro Business Loan (KUR) is a credit for financing productive business segment of micro, small, medium, and cooperative feasible but not yet bankable for working capital and / or investment credit through direct and indirect financing pattern (linkage) guaranteed by Lembaga Penjamin Kredit. This study aims to examine how the implementation of KUR distribution and its role in the empowerment of women. This research uses mixed methods method. The sample in this research was 71 respondents who were drawn using Taro Yamane formula with precision 0,1. The location of this research is PT. Bank Mandiri branch of Medan Iskandar Muda (Tbk). The results of this study show that the distribution system of KUR PT. Bank Mandiri branch of Medan Iskandar Muda (Tbk) through nine stages using the 5 C standard (Capital, Collateral, condition, character, capacity) as the implementation guideline. The results of the study of obtaining the KUR program have a good impact on the business development and personal debtor. This is because the survey system conducted on an ongoing basis by PT. Bank Mandiri branch of Medan Iskandar Muda (Tbk) forced the debtor to discipline in financial management.